Energy-Efficient and SLA-Based Resource Management in Cloud Data Centers - Altino Sampaio (2016)
Nowadays, cloud data centers play an important role in modern Information Technology (IT) infrastructures, being progressively adopted in different scenarios. The proliferation of cloud has led companies and resource providers to build large warehouse-sized data centers, in an effort to respond to costumers demand for computing resources. Operating with powerful data centers requires a significant amount of electrical power, which translates into more heat to dissipate, possible thermal imbalances, and increased electricity bills. On the other hand, as data centers grow in size and in complexity, failure events become norms instead of exceptions. However, failures contribute to the energy waste as well, since preceding work of terminated tasks is lost. Therefore, today's cloud data centers are faced with the challenge of reducing operational costs through improved energy utilization while provisioning dependable service to customers. This chapter discusses the causes of power and energy consumption in data centers. The advantages brought by cloud computing on the management of data center resources are discussed, and the state of the art on schemes and strategies to improve power and energy efficiency of computing resources is reviewed. A practical case of energy- efficient and service-level agreement (SLA)-based management of resources, which analyzes and discusses the performance of three state-of-the-art scheduling algorithms to improve energy efficiency, is also included. This chapter concludes with a review of open challenges on strategies to improve power and energy efficiency in data centers.